Giant Vein of Galen Malformation as a Cause of TIA- A Case Report - Lakhe, Prashant; Kutum, Chayanika; Mahajan, Mahesh; Singh, Daljit (Nepal Journal of Neuroscience, 2025)
Introduction: Vein of Galen malformations (VOGMs) are rare vascular entities originating from persistent shunting of primitive choroidal vessels into the median prosencephalic vein of Markowski. They usually present in infancy or childhood as seizures, hydrocephalus or cardiac failure; adult presentations are uncommon. In addition, giant VOGM in an adult is extremely rare to find. Case description: We present an exceedingly rare case of a giant VOGM measuring 3.4 x 3.7 x 3.2 cm in a 20-year-old female presenting as episodes of transient ischemic attack (TIA) which was obliterated successfully using endovascular embolization. Conclusion: VOGMs are associated with poor clinical outcome if left untreated. With advancement in endovascular techniques of obliteration, proper timely management can lead to good outcomes.